Online sharing of knowledge among in-service teachers for professional development purposes - Kosma, Panagiotis (My University, 2017)
New technologies and online resources for educational purposes inspire researchers to approach Professional Development (PD) from a different angle with the aim to professionally improve teachers' practices and methodologies. From this perspective, the broad use of online communities of practice (COPs) among teachers seems to be a common training model for in-service professional teachers. The utilization of communities of practice facilitates teachers' sharing of knowledge by creating opportunities for its members to interact and exchange good practices. The present study explores (a) the patterns of knowledge sharing amongst teachers in an official online community for PD purposes and (b) teachers' perceptions and motivation to participate in such online community. Data were collected through the analytics of the online community, in conjunction with questionnaires and interviews with community members. Results demonstrate that the most important motivation of teachers to participate in online community is the opportunity to share knowledge, ideas and successful practices. The paper discusses the potential training model through online communities of practice based on sharing of knowledge, aiming to contribute to PD research, shedding light to new challenges related to the PD of in-service teachers.
Keywords: Communities of practice; Online; Professional development; Sharing of knowledge; Teachers